'Allah has spoken to us: we must keep silent.' In the folds of secrecy, the Holy Book of the Druze. Issue 2 (3rd April 2018) - Armanet, Éléonore
ABSTRACT: This article explores the cultural dynamics of bond and separateness created around the Book of Wisdom ( kitâb əl-ḥikma ), the Druze Holy Book. The Text, unrevealable to Druze non-believers or foreigners, is shrouded in a collective pact to 'keep quiet'. I assert that this alliance aims to protect Druze intimacy rather than highlight their separateness from others. It is rooted in the Druze premise that meaning is both corporeal and feminine, that it pertains to an ineffable interiority. I thereby distance myself from anthropological analyses that consider the so-called Druze secret around the Book as static content solely related to language.